Parsec-scale radio morphology in Seyfert galaxies - Lal, D; Shastri, P; Gabuzda, D (2002)
We have observed a sample of Seyfert galaxies with global VLBI in order to test the predictions of the Unified Scheme for Seyferts, which hypothesises that Seyferts of type 1 and of type 2 differ only in the orientation of the axisymmetric active nucleus with respect to the observer. In this case, the parsec-scale radio structures of the two types should be similar. The 10 Seyfert 1s and 10 Seyfert 2s in our sample have been selected to have similar distributions of redshift and properties of their host galaxies: [OIII] luminosity, galaxy bulge luminosity etc. In this way, we ensure that the two subsamples of Seyferts are matched with respect to properties that axe expected to be orientation-independent. We are thus able to test the Unified Scheme rigorously. We detect all the objects that we observed and discuss the results. Our results are consistent with the prediction of the simple Unified Scheme.